An Enhanced Probabilistic Neural Network For Pattern Classification - Chang, Roy Kwang Yang (2010)
Pattern classifiers can be applied in a myriad of fields, ranging from machine condition monitoring to weather prediction. A pattern classifier that performs in a non stochastic manner, able to handle missing features and can manage high dimensionality, very much sought after. This is the motivation for this research and our proposed model was designed with those traits in mind.